A facile healing of two-step deposited MAPbI3 perovskite on TiO2 nanorod through dynamic methylamine treatment. (June 2022) - Chen, Yu-Sheng; Hung, Tung-Yu; Lo, Yuan-Shun; Wang, Chih-Liang
Abstract: The highly crystalline TiO2 nanorod as an underlying electron transport layer in perovskite solar cell has gained much attention due to its directional charge transport, better carrier extraction and enhanced light scattering. However, the morphology of perovskite film is critical to the photovoltaic performance, which makes it challenging to realize a high-quality perovskite film readily on an uneven nanorod-shaped underlying layer. In this regard, we develop a facile strategy to modify the two-step deposited methylammonium lead iodide (MAPbI3 ) film, deposited on hydrothermally synthesized TiO2 nanorod, by rapidly introducing methylamine vapor during the rotation, which enables another control to film planarization via a shear force induced by air flow, to investigate the influence of methylamine (MA) healing on such perovskite solar devices. The morphology and porosity of PbI2 on nanorod-based TiO2 are systemically studied by controlling the mixed solvent effect of dimethylformamide and dimethyl sulfoxide to satisfy a preferred PbI2 for the two-step deposited perovskite using TiO2 nanorod. The performance of such two-step deposited perovskite film after the developed MA treatment can be further improved, which suggests the occurrence of liquified MAPbI3 during the rotation to provide the positive healing effect on the film smoothness, pore infiltration, and unreacted PbI2 residues. The perovskite film after a long MA treatment is found to suffer from the formation of more defects or disorders than the defect tolerance in MAPbI3, which outweighs the healing advantages. Such a trend highlights the importance of delicately optimizing the developed MA treatment process, which can possibly achieve a high-performance perovskite solar cell of using two-step deposited MAPbI3 on TiO2 NR. Graphical Abstract: ga1